A review of the concept of the heart rate deflection point - Bodner, M. E.; Rhodes, E. C. (Sports Medicine, 2000)
The heart rate deflection point (HRDP) is a downward or upward change from the linear HR-work relationship evinced during progressive incremental exercise testing. The HRDP is reported to be coincident with the anaerobic threshold. In 1982, Conconi and colleagues suggested that this phenomenon could be used as a noninvasive method to assess the anaerobic threshold. These researchers developed a field test to assess the HRDP, which has become popularised as the 'Conconi test'. Concepts used to define and assess the anaerobic threshold as well as methodological procedures used to determine the HRDP are diverse in the literature and have contributed to controversy surrounding the HRDP concept. Although the HRDP may be assessed in either field or laboratory settings, the degree of HR deflection is highly dependent upon the type of protocol used. The validity of HRDP to assess the anaerobic threshold is uncertain, although a high degree of relationship exists between HRDP and the second lactate turnpoint. The HRDP appears to be reliable when a positive identification is made; however, not all studies report 100% reproducibility. Although the physiological mechanisms explaining the HRDP are unresolved, a relationship exists between the degree and direction of HRDP and left ventricular function. The HRDP has potential to be used for training regulation purposes. Clinically, it may be incorporated to set exercise intensity parameters for cardiac rehabilitation.